Kemampuan Berbagai Putih Telur Unggas Sebagai Kelator dalam Mengatasi Keracunan Logam Berat Timbal (THE ABILITY OF VARIOUS AVIAN EGG ALBUMEN AS A CHELATOR TO OVERCOME LEAD HEAVY METALS TOXICITY) - Mustika, Aulia Andi; ., Andriyanto; Wientarsih, Ietje; Margarita, Meilisa Lidya (Jurnal Veteriner, 2014)
Protein in albumen can be chelated and create strong bond with lead. The research was done toevaluate the speed of chelating process by local chicken egg, layers chicken egg, mojokerto duck egg, andpeking duck egg. The experiment was conducted by mixing lead acetat with albumen on 1:1 ratio. White eggconcentrations were divided into 25%, 50%, 75%, and 100%. Control group used 0% of albumen concentration(aquadestilate). Peking duck white egg had the fastest speed of protein chelation. Peking duck albumen by100% concentration had the fastest speed of chelation among the other egg used in experiment (p<0,05). Inconclusion, albumen can be used to overcome lead toxicity, with various speed of chelating process amongalbumen of various alvian.
Keywords: white egg, denaturation, chelation, lead